Generating Sensor Data Summaries to Communicate Change in Elder’s Health Status - Alexander, G. L.; Wilbik, A.; Keller, J. M.; Musterman, K. (Applied Clinical Informatics, 2014)
Background: Sensor systems detect critical health changes of frail residents in the community. However, sensor systems alone may not allow users to identify data trends fast enough. Linguistic summaries of sensor data describing elder activity in their apartment provide a useful solution so clinicians can respond quicker.Objectives: This paper describes two case studies of independent elders living with sensors in their assisted living apartment. Residents experienced declining health status and activity level over a period of approximately 24 months. Linguistic summaries were assessed iteratively by engineers and nurses working with the sensor system.Methods: We created summaries of activity data collected from sensors located in resident apartments during a period of health status change. Engineers distilled information from heterogeneous data sources including bedroom motion and bed restlessness sensors during the summarization process. Engineers used fuzzy measures to compare two different periods of nighttime activity. Using iterative approaches a registered nurse worked with the team to develop algorithms and short phrases that appropriately capture and describe changes in activity levels.Results: Total activity levels captured by sensors were graphed for two elderly residents experiencing health problems over a period of months. In the first case study (resident 3004), an elderly resident had knee surgery and onset of backspasms postoperatively. Graphed dissimilar measures show changes from baseline when backspasms occur. In the second case study (resident 3003), there were increased periods of bed restlessness before and after a resident had a major surgical procedure. During these periods, graphs of dissimilarity measures indicate that there were changes from usual baseline periods of restlessness postoperatively indicating the health problems were persisting. Nurse care coordination notes indicate these episodes were related to poor pain control.Conclusions: Summaries of activity change are useful for care coordinators to detect resident health status for community dwelling residents.Citation: Alexander GL, Wilbik A, Keller JM, Musterman K. Generating sensor data summaries to communicate change in elder’s health status. Appl Clin Inf 2014; 5: 73–84 http://dx.doi.org/10.4338/ACI-2013-07-RA-0050
Keywords: Sensors; health care technology; assisted living facilities; activities of daily living